Stochastic multivariable self-tuning tracker for non-Gaussian systems - Filipovic, Vojislav (Zielona Góra: Uniwersytet Zielonogórski)
This paper considers the properties of a minimum variance self-tuning tracker for MIMO systems described by ARMAX models. It is assumed that the stochastic noise has a non-Gaussian distribution. Such an assumption introduces into a recursive algorithm a nonlinear transformation of the prediction error.
Keywords: ARMAX model; self-tuning tracker; non-Gaussian noise; robust statistics; global stability; optimality